(untitled) (Semiárida, 2020)
The dry matter (DM) yield and plant composition of deferred cultivated com was studied near the city of V. Mercedes (San Luis Province; 33° 39’ S, 65° 22’ 0, and 505 m in altitude). A randomized complete block design with 4 replications was used. Three commercial cultivars in plots of 20.5 m2 were evaluated. Samples were taken when alter the grain became pasty and hard. Dry matter yield of the whole plant and its components (Ieaf, stem, and spike) was determined. Means were compared by analysis of variance using Duncan’s Multiple Range Test (P<0.05). Total yield differences among cultivars were nol found (mean= 12,164.4 kgDM/ha), bul differences in spike component yield were found. In sacco degradability of the leaf (L), leaf sheller (Sh) and slem (T) fraclions of one of the cultivars was evalualed. In sacco degradabilily expressed as % values al 72 h were 77.3, 71.1, 60.1 respectively, and differed significantly (P<0.05).